2013
DOI: 10.1103/physrevc.88.014314
|View full text |Cite
|
Sign up to set email alerts
|

Unification of Airy structure in inelasticα+16O scattering andα-cluster structure with core excitation in20

Abstract: The Airy structure of the nuclear rainbow and prerainbow in inelastic and elastic α + 16 O scattering is studied with the coupled channel method using a folding potential derived from the microscopic wave functions of 16 O. The theoretical calculations reproduce the characteristic energy evolution of the Airy minimum of the experimental angular distributions. The energy levels with α-cluster structure in 20 Ne are reproduced well using the potentials determined from the analysis of scattering. It is shown that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The phenomenon was first discussed in connection with 16 O(α,α) 16 O and 40 Ca(α,α) 40 Ca elastic scattering. For these reactions it was noticed later that the so-called anomalous cross sections are related to weak absorption of the doubly-magic target nuclei, and it is possible to describe the angular distributions within the OM [64][65][66][67][68][69]. Contrary to these findings, it turned out that the reproduction of the backward angular range in, e.g., 6 Li(α,α) 6 Li or 20 Ne(α,α) 20 Ne remains extremely difficult, and various explanations for the backward rise have been suggested: inelastic coupling to low-lying excited states, compound-elastic contributions, elastic α transfer, and angular-momentum-dependent absorption (e.g., [70][71][72][73]).…”
Section: Alas For 64 Zn?mentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon was first discussed in connection with 16 O(α,α) 16 O and 40 Ca(α,α) 40 Ca elastic scattering. For these reactions it was noticed later that the so-called anomalous cross sections are related to weak absorption of the doubly-magic target nuclei, and it is possible to describe the angular distributions within the OM [64][65][66][67][68][69]. Contrary to these findings, it turned out that the reproduction of the backward angular range in, e.g., 6 Li(α,α) 6 Li or 20 Ne(α,α) 20 Ne remains extremely difficult, and various explanations for the backward rise have been suggested: inelastic coupling to low-lying excited states, compound-elastic contributions, elastic α transfer, and angular-momentum-dependent absorption (e.g., [70][71][72][73]).…”
Section: Alas For 64 Zn?mentioning
confidence: 99%
“…Inelastic scattering leading to the first four exited states of 64 Zn was also measured in an angular range limited to a more backward region. Using the activation technique, the cross sections of the 64 Zn(α,γ ) 68 Ge, 64 Zn(α,n) 67 Ge, and 64 Zn(α,p) 67 Ga reactions were also measured at the same energies. Since the experimental techniques of both the scattering and activation experiments were already described in detail elsewhere [9,37], here only the most important features of the measurements and the results are presented.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Inelastic rainbow scattering has also been especially powerful in understanding the highly excited cluster structure near and above the threshold energy, such as the α particle condensation of the Hoyle state in 12 C and the Hoyle-analog state in 16 O [21][22][23][24][25]. A recent systematic study of the evolution of the Airy structure in inelastic scattering for the typical α+ 16 O system [26] showed that the cluster structure with core excitation in 20 Ne near the threshold energy region and the inelastic nuclear rainbow scattering can be understood in a unified way by using reliable interaction potentials for the inelastic channels. This urges us to study inelastic rainbow scattering with heavy ions in order to determine the interaction potentials in inelastic channels, which will make it possible to understand the molecular structure with core excitation, for which phenomenological shallow potentials have been used widely instead of a deep potential [27].…”
Section: O+mentioning
confidence: 99%
“…[21], which reproduces almost all the energy levels well up to E x ≈ 13 MeV and the electric transition probabilities in 16 O. The wave functions have been successfully used for the systematic analysis of elastic and inelastic α + 16 O scattering over a wide range of incident energies and the α cluster structure study of 20 Ne [22]. ρ 12 C, which is calculated using the microscopic three-α-cluster model in the resonating group method [23].…”
mentioning
confidence: 99%